Clinical Effectiveness of a Critical Care Nursing Outreach Service in Facilitating Discharge From the Intensive Care Unit - Williams, Teresa; Leslie, Gavin; Finn, J.; Brearley, L.; Asthifa, M.; Hay, B.; Laurie, K.; Leen, T.; O'Brien, K.; Stuart, M.; Watt, M. (American Association of Critical Care Nurses, 2010)
Background - Improved discharge planning and extension of care to the general care unit for patients transferring from intensive care may prevent readmission to the intensive care unit and prolonged hospital stays. Morbidity, mortality, and costs increase in readmitted intensive care patients. Objectives - To evaluate the clinical effectiveness of a critical care nursing outreach service in facilitating discharge from the intensive care unit and providing follow-up in general care areas. Methods - A before-and-after study design (with historical controls and a 6-month prospective intervention) was used to ascertain differences in clinical outcomes, length of stay, and cost/benefit. Patients admitted to intensive care units in 3 adult teaching hospitals were recruited. The service centered on follow-up visits by specialist intensive care nurses who reviewed and assessed patients who were to be or had been discharged to general care areas from the intensive care unit. Those nurses also provided education and clinical support to staff in general care areas.Results - In total, 1435 patients were discharged during the 6-month prospective period. Length of stay from the time of admission to the intensive care unit to hospital discharge (P = .85), readmissions during the same hospital admission (5.6% vs 5.4%, P = .83), and hospital survival (P = .80) did not differ from before to after the intervention. Conclusions - Although other studies have shown beneficial outcomes in Australia and the United Kingdom, we found no improvement in length of stay after admission to the intensive care unit, readmission rate, or hospital mortality after a critical care nursing outreach service was implemented.